Factors that impact environmental awareness among residents regarding the disposal of e-waste in Taman Desa Rasah / Farah Adilla Ab Rahman - Ab Rahman, Farah Adilla (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
E-waste, referring to discarded electronic equipment, parts, and materials, seriously threatens environmental sustainability and energy conservation. Raising community awareness about sustainable e-waste management is essential to address this issue. This article aims to assess the level of ecological consciousness in the Taman Desa Rasah community toward e-waste management. Two hundred participants were selected using a convenient sampling method in Seremban 3, Negeri Sembilan, and their feedback was collected via a questionnaire tool. The study revealed that while respondents had a high level of e-waste management knowledge, their attitudes and practices were only moderate. These findings can serve as a valuable reference for government, non-governmental organizations, authorities, and the community to establish a more sustainable and responsible approach to e-waste management in their community.